Meat Quality in Kosovo and Liaison with Consumers - Kovaçi, Idriz; Bushi, Fari; Tahiri, Alberta (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The purpose of this paper is to provide a professional analysis and reflection of the quality of meat and its products and its impact on consumer selection, we should also mention that meat and its products as one of the main elements in the consumer table has a special importance in economic analysis both in terms of quality and customer satisfaction as well as in terms of price and economic well-being.We should also mention that it is not in vain to say that regular and quality food is the safest guarantee for a consolidated health, but not to forget that it can not always be taken into account and added care that what we consume in different places like in social organizations or different parties.But food safety should be a vital issue and a priority over priority because the food quality refers to some specific characteristics such as nutrient content as well as organoleptic properties mainly related to the taste and processing of food, packaging and others.Also, do not forget to mention that the food must be suitable for consumption and not to result in any way in the consequences and to harm the health of the consumer.So it is primary to pay special attention to the risks we may encounter in food products in advance to be attentive and prepared for the risks and consequences or diseases born of food, a regular nutrition and quality food reflects half of the health of the human body.